Analyzing Barriers to Reverse Logistics Systems for E-Commerce in Vietnam - Tran, Thi Huong; Ngo, Thuy Dung; Pham, Thi Anh Tu (JST: Engineering And Technology For Sustainable Development, 2024)
Efficient reverse logistics management not only reduces costs but also plays a crucial role in creating added value for businesses and protecting the environment. The objective of this study is to explore and classify barriers and then prioritize them based on their importance using pairwise comparison methods. To this end, a two-stage mixed-methods research design was employed. The initial qualitative stage involved a comprehensive literature review to identify key themes and categorize them into five main barrier groups: government, organization and management methods, coordination in supply chain, finance and economics, and infrastructure. The subsequent quantitative stage utilized the Analytical Hierarchy Process (AHP) and Relative Importance Index (RII) to analyze and prioritize the specific barriers within these groups. The results show that the unclear organizational structure for reverse logistics activities, the lack of mechanisms and support from the government, and a lack of coordination from customers are the biggest barriers. This paper proposed solutions for the government and e-commerce businesses to eliminate barriers and operate efficiently reverse logistics systems.